2017
DOI: 10.1021/acs.est.7b00507
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Insight into the Reactivity of Chlorine-Derived Radicals in the Aqueous-Phase UV–Chlorine Advanced Oxidation Process: Quantum Mechanical Calculations

Abstract: The combined ultraviolet (UV) and free chlorine (UV-chlorine) advanced oxidation process that produces highly reactive hydroxyl radicals (HO) and chlorine radicals (Cl) is an attractive alternative to UV alone or chlorination for disinfection because of the destruction of a wide variety of organic compounds. However, concerns about the potential formation of chlorinated transformation products require an understanding of the radical-induced elementary reaction mechanisms and their reaction-rate constants. Whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
80
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(88 citation statements)
references
References 65 publications
5
80
0
Order By: Relevance
“…Recently, it was found that reaction rate constants of HO˙ and chlorine-derived radicals are linearly correlated with theoretically calculated free energies of activation [30,38]. Such a computational chemistry approach will be useful for a deeper understanding of reactivity of reactive radical species in UV/chlorine AOPs.…”
Section: Reactive Radical Speciesmentioning
confidence: 98%
See 3 more Smart Citations
“…Recently, it was found that reaction rate constants of HO˙ and chlorine-derived radicals are linearly correlated with theoretically calculated free energies of activation [30,38]. Such a computational chemistry approach will be useful for a deeper understanding of reactivity of reactive radical species in UV/chlorine AOPs.…”
Section: Reactive Radical Speciesmentioning
confidence: 98%
“…Therefore, it is important to elucidate the reactivity of each radical species with chemical compounds for understanding the efficacy of UV/chlorine AOPs. Table 2 summarizes reaction rate constants of HO˙, Cl˙, ClO˙, and Cl 2˙− with some chemicals reported in literatures [18,[24][25][26][27][28][29][30][31][32]. HO˙ has second-order reaction rate constants with approximately 10 9 -order level regardless of saturated compounds or benzene derivatives.…”
Section: Reactive Radical Speciesmentioning
confidence: 99%
See 2 more Smart Citations
“…Ozone also reacts with X 2 −• ( ). The ClO • radical appears to be much less reactive than X • and X 2 −• toward organic compounds [ 65 ].…”
Section: Reactions Of Rhsmentioning
confidence: 99%